Agrobacterium tumefaciens Deploys a Superfamily of Type VI Secretion DNase Effectors as Weapons for Interbacterial Competition In Planta - Ma,L-S; Hachani,A; Lin,J-S; Filloux,A; Lai,E-M (Cell Host & Microbe, 2014)
The type VI secretion system (T6SS) is a widespread molecular weapon deployed by many Proteobacteria to target effectors/toxins into both eukaryotic and prokaryotic cells. We report that Agrobacterium tumefaciens, a soil bacterium that triggers tumorigenesis in plants, produces a family of type VI DNase effectors (Tde) that are distinct from previously known polymorphic toxins and nucleases. Tde exhibits an antibacterial DNase activity that relies on a conserved HxxD motif and can be counteracted by a cognate immunity protein, Tdi. In vitro, A. tumefaciens T6SS could kill Escherichia coli but triggered a lethal counterattack by Pseudomonas aeruginosa upon injection of the Tde toxins. However, in an in planta coinfection assay, A. tumefaciens used Tde effectors to attack both siblings cells and P. aeruginosa to ultimately gain a competitive advantage. Such acquired T6SS-dependent fitness in vivo and conservation of Tde-Tdi couples in bacteria highlights a widespread antibacterial weapon beneficial for niche colonization.